2016
DOI: 10.3390/ijms17040581
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Microscopic Strategies towards the Analysis of the Cytoskeletal Networks in Major Neuropsychiatric Disorders

Abstract: Mental health disorders have become worldwide health priorities. It is estimated that in the next 20 years they will account for a 16 trillion United State dollars (US$) loss. Up to now, the underlying pathophysiology of psychiatric disorders remains elusive. Altered cytoskeleton proteins expression that may influence the assembly, organization and maintenance of cytoskeletal integrity has been reported in major depressive disorders, schizophrenia and to some extent bipolar disorders. The use of quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…For example, expression of FAK (focal adhesion kinase) was diminished in autistic lymphoblasts and overexpression of FAK in these cells restored the adhesion and migration defects . Besides ASDs, change in cytoskeleton proteins expression has been reported in other psychiatric disorders . In addition, recent genetic studies demonstrate that alterations in synaptic genes including those encoding cell adhesion molecules and their interaction partners play important roles in the pathogenesis of ASD .…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of FAK (focal adhesion kinase) was diminished in autistic lymphoblasts and overexpression of FAK in these cells restored the adhesion and migration defects . Besides ASDs, change in cytoskeleton proteins expression has been reported in other psychiatric disorders . In addition, recent genetic studies demonstrate that alterations in synaptic genes including those encoding cell adhesion molecules and their interaction partners play important roles in the pathogenesis of ASD .…”
Section: Discussionmentioning
confidence: 99%
“…In further support of the validity of this model, subsequent studies revealed defects in MAP6 expression in humans presenting developmental delay, corpus callosum dysgenesis, autistic or schizophrenic symptoms (Shimizu et al, 2006;Choi et al, 2009;Martins-de-Souza et al, 2009;Xiao et al, 2015;Coumans et al, 2016;Wei et al, 2016a,b;Chen et al, 2021).…”
Section: Map6 Ko Mice As a Model For The Study Of Schizophreniamentioning
confidence: 87%
“…Proteomic studies of the frontal cortex and anterior cingulate gyrus indicate the presence of abnormal cytoskeletal organization in depressed patients, which is associated with changes in the expression of, among others, glial fibrillary acidic protein (GFAP), tubulin isoforms or MAP proteins [72]. Suicide victims demonstrated the increased expression of mRNA and proteins such as TNF-alpha, IL-6 and IL1-beta in Brodmann's area 10, suggesting the involvement of pro-inflammatory cytokines in the pathogenesis of psychiatric disorders [73].…”
Section: Which Alterations Are Observed In the Depressed Brainmentioning
confidence: 99%